The development of a high pressure torsion test methodology for simulating wheel/rail contacts. (April 2021) - Evans, M.; Skipper, W.A.; Buckley-Johnstone, L.; Meierhofer, A.; Six, K.; Lewis, R.
Abstract: Simulating the wheel/rail contact of a train is traditionally conducted using small-scale twin-disc testing. Here an emerging alternative method, the "high pressure torsion" (HPT) test is introduced. This has advantages over twin-disc testing as only one cycle is used and it is easier to control third body layers during testing. Shear stress data generated is useful on its own, but can also be used to parameterise analytical prediction tools such as the extended creep force model (ECF), which produces creep-force curves from HPT data. This can then be validated against field data to develop a full-scale predictive capability. A detailed account of the HPT methodology development and the procedures for running a typical test are presented along with case studies that illustrate the typical output of HPT testing. Highlights: New test for simulating wheel/rail interface. Avoids recycling in current twin disc testing. Third-body layer more easily incorporated. Data can be used to parameterise models for full-scale predictions.